The Islamic External Critics of Public Administration: A Comparative Perspective (American Journal of Islam and Society, 1985)
"Whence did you enslave people who were born free?" (Umar Ibn-al-Khattab)The growth of public administration and the increasing influence ofadministrative agencies on public policy make the perennial politicalproblem of the control of administration more important than ever.Governmental activities nowadays touch so many people, in so manyways, that citizens' dissatisfaction with administration is inevitable.Many countries have sought protections and safeguards againstoppressive, mistaken, or careless exercise of public authority.Although the bureaucrats act as a leveling and rationalizing force,they are susceptible to certain persistent maladies. W.A. Robson hasidentified these as excessive sense of self-importance; indifference to thefeelings or convenience of others, obsessive to established practiceregardless of resulting hardships, persistent addiction to formality, andastigmatic inability to perceive the totality of the government because ofpreoccupation with one of its parts. When these maladies exist, theymay not be instantly recognized and treated, because administrativework often occurs beyond the gaze of professional observers. Moreover,many of the individuals with whom administrators deal offensively arelikely to be anonymous and the injustices invisible.The purpose of this study is to show that Islam had developedprominent external critics of administration long before the majorcountries had developed their current protective mechanisms againstbureaucratic excesses. The main objective is to integrate the majorIslamic critics of administration found in lslamic literature .andtheir current equivalent in modern countdea so that they become morecompatible with the contextual timing and demands of dailyadministrative life. A comparative approach will facilitate the ...